The Employment Effect of Industry-Specific, Collectively-Bargained Minimum Wages - Hanna Frings (Rheinisch-Westfälisches Institut für Wirtschaftsforschung (RWI), 2012)
This paper estimates the employment effects of industry-specific, collectively-bargained minimum wages in Germany for two occupations associated with the construction sector. I propose a truly exogenous control group in contrast to the control group design used in the literature. Further, a difference-in-differences-in-differences estimator is presented as a robustness test for occupation-specific and/or industry-specific, timevarying, unobserved heterogeneity. I do not find a significantly negative employment effect, even though the minimum wage is binding in (East) Germany. This result can be explained by substitution effects, noncompliance and models of monopsonic competition. – – Diese Studie untersucht die Beschäftigungseffekte von Branchen -spezifischen Mindestlöhnen, die durch Tarifverhandlungen gesetzt werden, für zwei Berufsgruppen, die der Baubranche angehören. Im Gegensatz zu den üblichen Ansätzen in der Literatur, wird eine exogene Kontrollgruppe verwendet, die nicht durch das Treatment beeinflusst wird. Des Weiteren stellt ein Differenz-von-Differenzen-von-Differenzen Schätzer einen Robustheitstest dar, der für zeitvariante, unbeobachtbare Heterogenität in der Berufsgruppe oder im Wirtschaftszweig kontrolliert. Ich finde keine signifikanten, negativen Beschäftigungseffekte, obwohl der Mindestlohn in (Ost-)Deutschland bindend ist. Dieses Ergebnis kann durch Substitutionseffekte, Umgehungsstrategien und die moderne Monopsontheorie erklärt werden.
Keywords: J38; J42; 330; Minimum wage; monopsonic competition; difference-in-differences